PENGARUH PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERATING - Iwan Setiawan; Fifi Swandari; Dian Masita Dewi (Universitas Lambung Mangkurat, 2018)
This study aims to examine the influence of Islamic Social Reporting (ISR) disclosure on corporate value and the influence of financial performance in moderating the disclosure of Islamic Social Reporting (ISR) on corporate value through media annual report. This research is expected to increase the repertoire of science in the field of financial management, especially about the influence of Islamic social responsibility disclosure to corporate value and financial performance in moderating the influence of Islamic Social Reporting (ISR) on corporate value. This study was conducted on the annual report of 25 sharia issuers incorporated in the Jakarta Islamic Index (JII) during the period 2013-2016. Hypothesis testing used regression techniques with moderating variable. The results of this study indicate that Islamic Social Reporting (ISR) affect the corporate value. Listed Sharia issuers in the Jakarta Islamic Index (JII) are able to provide information on corporate social responsibility disclosure in annual report to increase stakeholders' trust in the sharia system applied in the company in order to increase the corporate value in the eyes of stakeholders, although none of the companies disclose information completely. Financial performance may not be able to moderate the influence of Islamic Social Reporting (ISR) on corporate value. It is alleged that Islamic Social Reporting (ISR) is able to moderate the influence of financial performance on the corporate value